Thermal properties and flame retardancy of an ether-type UV-cured polyurethane coating (eXPRESS Polymer Letters)
A new UV-reactive monomer piperazine-N,N′-bis(acryloxyethylaryl-phosphoramidate) (N-PBAAP) containing phosphorus and nitrogen was synthesized and used as flame retardant for an ether-type UV-cured polyurethane acrylate (PUA) coating. The thermal properties of the PUA films were investigated by thermogravimetric analysis (TGA) in air and nitrogen atmosphere. The TGA results showed that the incorporation of N-PBAAP can obviously enhance the char residue of the PUA coatings. From the TGA and real time Fourier transformed infrared spectroscopy (RT-FTIR) results, different degradation behaviors were observed in the PUA coatings with different N-PBAAP content. The combustibility of the PUA coatings was evaluated by microscale combustion calorimeter (MCC). The MCC results revealed that the addition of NPBAAP in the coatings can significantly reduce the peak Heat Release Rate (pHRR), Heat Release Capacity (HRC) and the Total Heat Release (THR) of the samples. Furthermore, dynamical mechanical thermal analysis (DMA) was employed to examine the viscoelastic properties of the PUA films. It was found that the incorporation of N-PBAAP in the formulation can bring in more functional groups to the coatings, which results in an increase of the glass transition temperature (Tg) and cross linking density (XLD) of the films.